Sitora SEMANTIC DEVELOPMENT OF DIRECTIONAL VERBS IN OLD ENGLISH: SEMANTIC DEVELOPMENT OF DIRECTIONAL VERBS IN OLD ENGLISH - Mardonova, Sitora (Журнал иностранных языков и лингвистики, 2022)
This article analyzes the semantic development of some action verbs in English, based on which to determine the specific semantic occurrence of walking verbs. The focus is on defining the structure and boundaries of the semantic verbs of movement, that is, defining the semantic field of these verbs and the semantic classification of these verb lexemes to identify their common, unifying, distinguishing semantics.